CURRENTLY MOST RELEVANT ISSUES IN PEDAGOGY AND THEIR SIGNIFICANCE IN HIGHER EDUCATION (CANADA - SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2026)
This article presents an in-depth and extended analysis of the most relevant issues in contemporary pedagogy within the context of higher education. The study focuses on digital pedagogy, student-centered learning, competency-based education, inclusive education, quality assurance mechanisms, and the continuous professional development of higher education teachers. These pedagogical approaches are analyzed from both theoretical and practical perspectives, emphasizing their role in improving the effectiveness, accessibility, and sustainability of higher education systems [1][2].